GHD advertising campaign across cultures. A case study - Maci, Stefania M. (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2006)
The type of advertisements addressed to young people seem to reinforce values conveyed by music, films and fashion. In this new cultural trend, GHD advertising apparently proceeds in an opposite direction, as the visual element of the new GHD advertising campaign is strongly interrelated with religion. Yet the new religious values GHD is offering appear to be more in line with urban trends than with asceticism. It is the aim of this paper to illustrate how the GHD advertising campaign in the UK establishes the identity and success thanks to intertextuality. I will further compare the same ad as it appeared in the Italian press and will point out how the GHD Italian version not only loses its grasp of religion but is also less incisive in style than the English advertisement text. The result is a text in strong opposition to the visual it is linked with.